1973
DOI: 10.1159/000259823
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interindividual Observations on Fluoride Ion Activity and Retained Fluoride with Sodium Fluoride Mouth Rinses

Abstract: 2-min mouth rinses with 7 and 10 ml 0.05% NaF were carried out by 9 adults and 24 children (10–11 years old). Each person rinsed 5 times with , fluoride each volume. The oral expectorate with the rinsing solu tion was then weighed. The fluoride ion activity of the expectorates was determined, and retention of fluoride (μg and %) was calculated. Significantly higher fluoride ion activity with 10 than with 7 ml was obtained both by the adults (14.7 ± 6.5 ppm F-) and the children (9.0 ± 5.7 ppm F-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…Ericson and Forsman [1969] looked at reten tion in 4-to 7-year old children and showed 26% of a 0.1 % fluoride paste to be retained. This figure is higher than that re ported by Bossert and Dunning [1945] (3-11% retention) and Birkeland [1973] (13-15% retention) after use of fluoride mouthrinses, but lower than that of Hellstrom [1960], who showed 30% retention following use of a 0.1% sodium fluoride mouthwash.…”
contrasting
confidence: 55%
“…Ericson and Forsman [1969] looked at reten tion in 4-to 7-year old children and showed 26% of a 0.1 % fluoride paste to be retained. This figure is higher than that re ported by Bossert and Dunning [1945] (3-11% retention) and Birkeland [1973] (13-15% retention) after use of fluoride mouthrinses, but lower than that of Hellstrom [1960], who showed 30% retention following use of a 0.1% sodium fluoride mouthwash.…”
contrasting
confidence: 55%
“…It has been shown that young children may retain some solution when they rinse (Hellstrom, 1960;Ericsson and Forsman, 1969;Birkland, 1973;Wei and Kanellis, 1983). The daily use of an over-the-counter rinse containing 225 ppm F [ mg F/5 mL] could produce or contribute to fluorosis in age-susceptible children, depending upon the total amount of bioavailable fluoride being consumed.…”
Section: Risksmentioning
confidence: 99%
“…It cannot be ruled out that the F rinses in the control group might have contributed to the preeruptive uptake of fluoride in the enamel. Thus, it has been shown [Birkeland, 1973] that about 15% of the fluoride in 10 ml of a 0.2% NaF solu tion is retained by young schoolchildren after mouthrinsing. Flowever, this intake of fluoride from 40 rinses in the control group would make a total of about 60 mg F as compared to 225 mg F in the supple ment group.…”
mentioning
confidence: 99%